Natural Stings: Selling Distrust About Vaccines on Brazilian YouTube - Tokojima Machado, Dayane Fumiyo; de Siqueira, Alexandre Fioravante; Gitahy, Leda (Frontiers in Communication, 2020)
In this study, we investigate YouTube’s videos related to vaccines to understand the particularities of the opposition to vaccines in Brazil. The World Health Organization considered vaccine hesitation as one of the greatest threats to global health in 2019. Researchers associated this hesitation to a strengthening of the anti-vaccination movements, suggesting that social media is currently the main spreader of this position. YouTube increasingly becomes a matter of concern, since its recommendation system is identified as a promoter of misinformation and extreme content. Despite YouTube’s statements, misinformation and disinformation (M&D) about vaccines continue to be disseminated in videos in Portuguese, reaching a large audience. We found 52 videos containing M&D about vaccines. The main M&D were the claim of dangerous ingredients in vaccines, the defense of self-direction — freedom of choice, independent research —, the promotion of alternative health services, the myth that vaccines cause diseases, conspiracy theories, and the allegation of vaccine’s severe collateral effects. We identified 39 brands advertising on 13 videos of our M&D sample. Although the YouTube Partner Program is an important source of income, the channels use different economic strategies, such as the selling of courses, and therapies and the use of fundraising platforms. We also found that alternative health channels spread distrust about traditional institutions to promote themselves as trusted sources for the audience and thereby profit with alternative health services.